Effects of a lifestyle counselling intervention on adherence to lifestyle changes 7 years after stroke – A quasi‐experimental study. Issue 1 (29th June 2022) - Oikarinen, Anne; Engblom, Janne; Paukkonen, Leila; Kääriäinen, Maria; Kaakinen, Pirjo; Kähkönen, Outi
Abstract: Background: Adherence to medication and healthy lifestyle is crucial for preventing secondary strokes and other vascular events. However, there is not enough evidence on the long‐term effects of hospital‐initiated lifestyle counselling. Aim: To determine the effects of The Risk Factor Targeted Lifestyle Counselling Intervention, which is implemented during acute hospitalisation, on adherence to lifestyle changes 7 years after stroke or TIA. Methods: Quasi‐experimental design with 7‐year follow‐up period. Baseline data ( n  = 150) were gathered from a neurology unit in Finland between 2010 and 2011. Patients received either the studied intervention ( n  = 75) or the prevailing form of counselling at the time ( n  = 75). Data concerning lifestyle and clinical values were measured at the baseline time point, while adherence to lifestyle changes was assessed 7 years later (2017–2018). Analysis of covariance and multivariate ordinal logistic regression were used to describe the mean differences between the intervention and control groups. Results: Several between‐group differences were detected, namely, members of the intervention group reported consuming less alcohol and having lost more weight during hospitalisation relative to the control group. No between‐group differences in the prevalence of smokers were found, but the intervention group reported a greater number of daily cigarettes than the control group. Adherence to medication, importance of adherence to a healthy lifestyle, support from family and friends, and support from nurses were all significantly higher in the intervention group than in the control group. Conclusions: The results suggest that the lifestyle counselling intervention was effective in decreasing alcohol use and weight, as well as increasing factors that are known to support adherence to a healthy lifestyle. Relevance to clinical practice: The results indicate that the adherence process already begins during acute phase counselling. To ensure long‐lasting lifestyle changes, counselling should be started at the hospital, after which it can be provided by friends and family members.